A Study on Impact of Government Schemes on Indian Economy: Exploring Government Schemes and Economic Impact in the COVID-19 Era (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In 2020, the world was threatened by a new COVID-19 virus, which threatened all – mobility, stability and the regular existence. In fact, this provided India and the planet with the biggest economic threat in a century. Public health strategy has been established as a solution or vaccine to combat this overwhelming problem. The need for the curve of the disease to flatten was related to the cost of livelihoods of a lower recession which stemmed from the constraints of the pandemic's economic locks. This inherent exchange contributed to life versus livelihoods political dilemma. Governments and central banks worldwide have utilised numerous policy mechanisms to support their economies, including lowering main policy rates, quantitative stimulus initiatives, debt subsidies, currency flows and financial rewards. India acknowledged the destructive effects of the pandemic and defined a peculiar direction among dreadful predictions by a variety of foreign organisations, owing to the large economy, the high population rate, and a heavy system for health.